Efektivitas Sistem Pengendalian Intern Atas Pengelolaan Subsidi Pada Badan Usaha Milik Negara - Tri Marhendra Rahardyan; Dhian Adhetiya Safitra; Afif Hanifah (Polytechnic of State Finance STAN, 2022)
This study groups patterns to identify deficiencies experienced by SOEs in Indonesia based on the findings of the BPK published in the IHPS ( Summary of Semester Audit Results) with a focus on subsidy management. This study aims to identify the pattern of BPK's findings related to the recurring problem of subsidy management on the performance of BUMN in Indonesia to provide an overview of BUMN managers in the future. The research data source is limited to IHPS from 2016 to 2018 (published by BPK in 2019) or before the Covid-19 pandemic. This study found that there are problems with weaknesses in the Internal Control System (SPI), which are still the findings with the most significant number, and the trend is increasing. In addition, the themes of the examination of Revenue, Costs, and Investments, Operations of SOEs, and Management of Subsidies are the findings of the investigation of the SPI of SOEs that repeatedly appear with a number of significant problems. Specifically regarding Subsidy Management, several themes of findings often occur, including SOPs that have not been prepared/incomplete, SOPs that have not been running optimally, and SOPs that are not adhered to. To overcome these problems, BUMN managers need to pay attention to the implementation of SPI, especially in the implementation of the complete preparation of SOPs and their implementation, which must be monitored so that they are adhered to, and the subsidy management business process can run optimally. Keywords: IHPS BPK, Internal Control, Management of Subsidies, Performance of SOEs